Improving trajectories of amphibians in wildlife passages - Testud, Guillaume; Canonne, Coline; Le Petitcorps, Quentin; Picard, Damien; Lengagne, Thierry; Labarraque, Dorothée; Miaud, Claude (Frontiers in Ecology and Evolution, 2022)
Linear transport infrastructure can alter the viability of populations and wildlife passages are used to mitigate their impacts. The assessment of their outcomes is often limited to recording the use of the tunnels by a focal species. For amphibians, the effectiveness of tunnels is poorly evaluated with little information about whether certain features encourage individuals that may be reluctant to pass through tunnels. One study showed that acoustic enrichment with anuran calls can increase the crossing of tunnels by newts. This study recorded the behavior of three European amphibian species in 3 tunnels, tracking them with pit- tags and detection with four RFID antennas installed on the floor of the tunnels. We tested (1) the effectiveness of the antennas in detecting the species, (2) the effect of the length of the tunnels, and (3) the effect of acoustic enrichment. Using a multi-state capture–recapture model, we evaluated the probability of an individual advancing between the tunnel sections. The effectiveness of the antennas varied according to species, higher for Urodela species than for Anuran species. Several types of paths were detected (constant and varying speeds, halt, and back-and-forth movements). The fire salamander and the great crested newt individuals exhibited a similar variety of movements in the tunnels (21 and 40 m length). T. cristatus made similar movements in the tunnels with and without acoustic enrichment. In water frogs, all the individuals (n=16) made a complete crossing in the tunnel with enrichment vs 75% (n=71) in the tunnel without enrichment. In T. cristatus, the probability of going forward at the entrance of the tunnel was 18% higher with enrichment in one tunnel. No significant effect of acoustic enrichment was observed in 2 others tunnels for this species. In Pelophylax esculentus, this probability was 78% higher in the tunnel with enrichment. This multi-antenna RFID system was able to provide valuable information on the behavior of these small animals when traversing the tunnels, as well as to test the effectiveness of tunnel features. The findings indicate that acoustic enrichment to attract animals to specific locations holds promise as a new conservation tool.